Testing as a Certification Approach - Simões, Alberto; Carvalho, Nuno; Almeida, José (Electronic Communications of the EASST, 2010)
For years, one of the main reasons to buy commercial software instead of adopting open-source applications was the, supposed, guarantee of quality. Unfortunately that was rarely true and, fortunately, open-source projects soon adopted some good practices in their code development that lead to better tested software and therefore higher quality products.In this article we provide a guided tour of some of the best practices that have been implemented in the Perl community in the recent years, as the pathway to a better community oriented repository of modules, with automatic distributed testing in different platforms and architectures, and with automatic quality measures calculation.